Synthesis and conductive properties of FeCI-oxidized polypyrrole on bacterial cellulose and phenol-formaldehyde resole resin substrates. - Magdaug, Robert L. (Miagao, Iloilo University of the Philippines in the Visayas, 2008)
Phenol-formaldehyde resin - polypyrrole composites were synthesized following the sequence of PF resin prepolymer synthesis by addition of pyrrole monomer, thermosetting on a petri dish then oxidation, and the other by PF resin prepolymer synthesis, addition monomer, oxidation then thermosetting. Bothe materials showed some conductivity but were nonhomogenous and was discontinued for further study., Polypyrrole was incorporated onto bacterial (BC) matrix by impregnating pyrrole onto the fiber followed by oxidation with FeCl3. Investigation of synthesis conditions included varying concentrations of pyrrole soaking solution, varying the oxidation time for pyrrole, varying the soaking times and determining the effect of moisture on the conductivity of the composite. Conductivity test on thin film strips using two probe technique show directly proportional relationship with increasing concentrations of pyrrole soaking solution, oxidation period, decreasing moisture content and soaking time of BC in pyrrole solution. Tensile strength tests show that as higher concentration of pyrrole is used there is reduction in strength. As moisture of the material decreases the tensile strength increase down to about 50 percent moisture after which the strength decreases. FT-IR spectra of samples show that BC-PPy is a composite material with pyrrole being adsorbed to the surface of cellulose fibers prior to oxidation to polypyrrole. The conductivity of the material is dependent on the quantity of polypyrrole in the BC but the amount of PPy deposition affects the strength of the composite.
Special Problem (Graduate, Degree of Master of Chemistry) -- College of Arts and Sciences, University of the Philippines in the Visayas, April 2008.
Keywords: Synthesis and conductive properties